INVESTIGASI TENTANG BUDAYA ORGANISASI, KEPUASAN KERJA, DAN KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI KARYAWAN BANK BJB CABANG TEGAL - Ari Deva Nanda; Taofik Hidajat (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
This study aims to determine how much influence the organizational culture, job satisfaction, and employee performance through organizational commitment. The population in this study were all employees of the Tegal branch bank bjb of 52 people. In this study the entire population was taken as a sample (census). The results of the analysis show that organizational culture directly has a positive influence on organizational commitment, job satisfaction directly has a positive effect on organizational commitment, organizational culture directly has a positive influence on employee performance, job satisfaction directly has a positive effect on employee performance, organizational commitment directly has a positive influence on employee performance, organizational commitment mediates the influence of organizational culture on employee performance, and organizational commitment mediates the effect of job satisfaction on employee performance.